The Association between the LPA Gene Polymorphism and Coronary Artery Disease in Chinese Han Population - Song, Zi-Kai (Hindawi Publishing Corporation, 2014)
Lp(a) has been well known as an independent risk factor for coronary artery disease (CAD). The LPA gene, as it encodes apo(a) of the Lp(a) lipoprotein particle, was associated with increased risk of CAD. The purpose of this study was to analyze the relationship between the polymorphisms of LPA gene and CAD in Chinese Han population. Five SNPs (rs1367211, rs3127596, rs6415085, rs9347438, and rs9364559) in the LPA gene were genotyped using Sequenom MassARRAY time-of-flight mass spectrometer (TOF) in 560 CAD patients as case group and 531 non-CAD subjects as control group. The numbers of these two groups were from Chinese Han ancestry. The results showed that allele (P = 0.046) and genotype (P = 0.026) of rs9364559 in the LPA gene was associated with CAD. The frequency of rs9364559 minor allele (G) in case group was obviously higher than that in control group. Results of haplotype analysis showed that 4 haplotypes which contained rs9364559-G were associated with increased risk of CAD in this population. This study explored rs9364559 in the LPA gene may be associated with the pathogenesis of CAD; and the risk of CAD might be higher in the population carrying 4 haplotypes of different blocks in the LPA gene.